Microstructurally sensitive crack nucleation around inclusions in powder metallurgy nickel-based superalloys. (15th September 2016) - Jiang, J.; Yang, J.; Zhang, T.; Zou, J.; Wang, Y.; Dunne, F.P.E.; Britton, T.B.
Abstract: Nickel-based superalloys are used in high strength, high-value applications, such as gas turbine discs in aero engines. In these applications the integrity of the disc is critical and therefore understanding crack initiation mechanisms is of high importance. With an increasing trend towards powder metallurgy routes for discs, sometimes unwanted non-metallic inclusions are introduced during manufacture. These inclusions vary in size from ∼10 μm to 200 μm which is comparable to the grain size of the nickel-based superalloys. Cracks often initiate near these inclusions, and the precise size, shape, location and path of these cracks are microstructurally sensitive. In this study, we focus on crack initiation at the microstructural length scale using a controlled three-point bend test, with the inclusion deliberately located within the tensile fibre of the beam. Electron backscatter diffraction (EBSD) is combined with high spatial resolution digital image correlation (HR-DIC) to explore full field plastic strain distributions, together with finite element modelling, to understand the micro-crack nucleation mechanisms. This full field information and controlled sample geometry enable us to systematically test crack nucleation criteria. We find that a combined stored energy and dislocation density provide promising results. These findings potentially facilitate more reliable and accurate lifing prediction tools to be developed and applied to engineering components. Graphical abstract: Highlights: High resolution digital image correlation. High resolution electron backscatter diffraction. Crack nucleation. Non-metallic inclusion.